Woman Existence Reflected In Laksmi Pamuntjak's The Questions Of Red Novels (2014): A Liberal Feminist Approach - Khoiriyah, Nidaul, Dr. Abdillah Nugroho, M.Hum (2017)
This research aims to analyze Woman Existence of Amba, reflected on Laksmi Pamuntjak's The Questions of Red novel, the purpose of the research is reveal what is woman existence , how is woman existence reflected in Laksmi Pamuntjak's novel using Liberal feminist Approach. The type of this research is qualitative research. The researcher took the data from the novel include the narration, monologue, and dialogue. The techniques of collecting the data is using library research, and the technique of the data analysis is using descriptive analysis which comprises procedures: data collecting, data display, and conclusion. Problem statement of the research is " How is woman existence reflected at laksmipamuntjak'sThe Question of Red novel ?" and the result of this research show: 1) Amba's struggle to get her existence leads her to become an independent woman and has a high self confidence. 2) the use of the woman existence gives strength to Amba to face her problems.